EKSTRAK ETANOL KULIT BUAH RAMBUTAN (NEPHELIUM LAPPACEUM) SEBAGAI INDIKATOR ALAMI TITRASI ASAM BASA - Aprilia, Ade Yeni (P3M STIKes Bakti Tunas Husada, 2019)
Natural indicators containing anthocyanin compounds can be used as natural indicators in acid-base titration,for example in Rambutan (Nephelium lappaceum) rind. This is because there wa a change in the structure ofanthocyanin at each interval of degrees of acidity (pH) which causes a change in color. The purpose of thisstudy was to determine the ability of rambutan peel as a natural indicator in acid-base titration. The simplicis oframbutan peel was extracted using maceration method with ethanol solvent: HCl 1% (9: 1), then anthocyaninProof Test on simplicia and extracts, wavelength determination and visual determination of pH tranyek. Thenthe indicator is applied to the acid-base titration. Based on the results of this study it was found that therambutan fruit extract yields a yield of 56.7%. For anthocyanin proof test on simplicia and the ethanol extractof rambutan fruit skin contains anthocyanin compounds with a wavelength of 529 nm. In the pH test of the pH 1-12 buffer solution results were obtained that the ethanol extract of Rambutan rind (Nephelium lappaceum)produced a color change at pH 1-3 red while at pH 6-8 produced a dark brown color as the natural pHindicator route. The results of the application of the ethanol extract of rambutan peel on acid-base titrationshowed that the indicator of Rambutan peel extract had a volume of NaOH which was almost the same as theBuilder Indicator, the Phenofthalein Indicator which was 18 mL. Ethanol extract of Rambutan Fruit Skin can beused as a natural indicator in acid-base titration